Secret and Impure Things: An Outline of the Problems and the Role of the Family in the Sexual Educationof Children in the Second Half of the 19th and Early 20th Century. Outline of problems - Nawrot-Borowska, Monika (Uniwersytet Wrocławski, 2013)
The aim of this analysis is an attempt to reproduce the commendations that the authors of the guides directed to parents and other family members in reference to sexual education of children and to show the evolution that occurred in the indicated problems during the period. Guides in the field of education, health, and hygiene of children constitute the source material used for the study. Research results indicate that development and operation in the field of child sexuality is influenced by many factors, which is why instructions that family should respect involved many aspects of life – sleeping, eating, clothing, leisure activities(games and toys, reading materials, proper company), etc. Counselling concentrated in main measure on aspects of a child’s sexual awareness and preventing masturbation.
Keywords: family; education; upbringing; sexual education; children; reference book